Implementation of The Independent Curriculum Teaching Module in Strengthening The Pancasila Student Profile - Rizky Eliandi; Anna Fitri Hindriana; Zaenal Abidin (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2026)
The purpose of this research is to produce teaching modules that are effective in strengthening the student profile of Pancasila through an active learning approach. The research method used is R&D (Research and Development) with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). Data were collected through learning style questionnaires and experiments in experimental and control classes. The questionnaire was used to measure the mutual cooperation dimension, while the test was used for students' critical thinking. Data analysis was carried out quantitatively using descriptive statistics to describe the learning outcomes of students before and after the application of teaching modules. Hypothesis testing was conducted using the Wilcoxon test to determine significant differences between the experimental and control groups. The results show that the application of teaching modules based on the Merdeka Curriculum can increase students' interest in learning and critical thinking skills in the experimental class compared to the control class. The experimental group's posttest score was significantly higher than the control group. The development of teaching modules based on the characteristics of students has proven to be valid and effective in achieving learning objectives. This can be seen from the increase in affective (mutual cooperation & critical thinking dimensions) and cognitive (formative assessment results) values.